2023
DOI: 10.1039/d2an01499h
|View full text |Cite|
|
Sign up to set email alerts
|

Smartphone-read phage lateral flow assay for point-of-care detection of infection

Abstract: The COVID-19 pandemic has highlighted the urgent need for sensitive, affordable, and widely accessible testing at the point of care. Here we demonstrate a new, universal LFA platform technology using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Unfortunately, most LFA formats of sufficient sensitivity are poorly suited for widespread home self-testing, including organic fluorophores, europium chelates, , up-converting phosphors, and quantum dots that offer high analytical sensitivity but require a complex apparatus for excitation/detection , and/or are unstable, photobleachable, or require narrow excitation/emission wavelengths . Enzyme-based chemiluminescent LFAs can provide ultrasensitive analysis but require often-unstable reporter substrates.…”
Section: Glow Lfa: From Inception To a Manufacturable Productmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, most LFA formats of sufficient sensitivity are poorly suited for widespread home self-testing, including organic fluorophores, europium chelates, , up-converting phosphors, and quantum dots that offer high analytical sensitivity but require a complex apparatus for excitation/detection , and/or are unstable, photobleachable, or require narrow excitation/emission wavelengths . Enzyme-based chemiluminescent LFAs can provide ultrasensitive analysis but require often-unstable reporter substrates.…”
Section: Glow Lfa: From Inception To a Manufacturable Productmentioning
confidence: 99%
“…The analyte concentration of 280 TCID50/mL was further tested in five replicates to confirm the LoD (Figure C). We adapted the Yale SalivaDirect PCR assay, which circumvents RNA extraction, and performed RT-PCR in house directly on nasal swab extracts to benchmark serially diluted pooled samples during LFA optimization and to check occasional fresh nasal specimens. There is no general consensus on the required analytical sensitivity to ensure clinical utility, but our Glow LFA was described by RADx as being (at that time) “the second most sensitive LFA” in the program, with the most sensitive being a commercial test based on the glow-in-the-dark nanophosphors previously developed in the Willson laboratory, with a reported LoD of 82 TCID50/mL. , …”
Section: Development Of the Sars-cov-2 Glow Lfa Prototypementioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of CL detection with the smartphone camera has been also investigated. Chabi et al [123] reported an LFIA platform employing phage-based CL reporters, combined with smartphone detection and applied to the diagnosis of SARS-CoV-2. Exploiting the same approach, Ren et al [124], trying to increase the sensitivity of the system, proposed a CL-LFIA based on the synthesis of the Au NP-antibody-HRP-polyethylene glyco conjugate for detecting cardiac troponin I (Figure 3b).…”
Section: Paper-based Diagnostic Devicesmentioning
confidence: 99%
“…The implementation of CL detection with smartphone camera has been also investigated. Chabi et al [116] reported a LFIA platform employing phage-based CL reporters, combined with smartphone detection and applied to the diagnosis of SARS-CoV-2. Exploiting the same approach Ren et al [117] trying to increase the sensitivity of the system, proposed a CL-LFIA based on the synthesis of the Au NP-antibody-HRP-polyethylene glycol conjugate for detecting cardiac troponin I (Figure 3b).…”
Section: Paper-based Diagnostic Devicesmentioning
confidence: 99%